Venous thromboembolism in non-critically ill patients with COVID-19 infection. Issue 193 (September 2020) - Trimaille, Antonin; Curtiaud, Anaïs; Marchandot, Benjamin; Matsushita, Kensuke; Sato, Chisato; Leonard-Lorant, Ian; Sattler, Laurent; Grunebaum, Lelia; Ohana, Mickaël; Von Hunolstein, Jean-Jacques; Andres, Emmanuel; Goichot, Bernard; et al.
Graphical abstract: Unlabelled Image Highlights: Venous thromboembolism (VTE) is a frequent complication in COVID-19 patients. Single-center study of COVID-19 patients admitted to general ward. 17.0% of patients with VTE Lack of thromboprophylaxis and leukocytosis were independent risk factors of VTE. VTE is independently associated with worse in-hospital outcomes.